APPLICATION OF THE SYSTEM OF LINEAR EQUATIONS TO ECONOMIC PROBLEMS - Taymanova E. L. (Web of Journals Publishing, 2024)
Nowadays, an economist with a high level of education must have mathematical knowledge. Because many issues of economics are directly related to the linear algebra course of mathematics. In this regard, the section on the system of linear equations is especially important. In this article, a mathematical model of economic problems resulting in a number of linear equations has been developed.
Keywords: system of linear equations, method of solving system of linear equations, method Kramer, determinants.